A GENOCIDE ANATOMY- THE RED FAMINE IN KAZAKHSTAN - Veysel İbrahim Karaca (Uluslararası Türk Lehçe Araştırmaları Dergisi, 2017)
In this study, the book titled "The Red Famine in Kazakhstan", which deals with the famine catastrophes in Kazakhstan between 1929 and 1933, was tried to be introduced. The book was written by Vahit Türk and Damira İbrahim in October 2016 and published by Bilge Culture and Art Publications. The work has been designed by the authors in three sections; "Letters and Documents", "Memories" and "Review and Interviews" is the title of.